Pemanfaatan Tanah Blangket Sebagai Bahan Campuran Paving Block Dengan Tinjauan Kuat Tekan - Pamungkas, Nur Setiaji (Politeknik Negeri Semarang, 2013)
In today's society infrastructure development , especially in the field of housing and there's also a supporting infrastructure utilization and the use of paving blocks as a construction material . This is because the use of paving blocks are generally considered less expensive and easy execution. Blangket soil can be categorized as one of the kinds of soils containing lime , which is the precipitate formed by chemical processes or mechanisms in nature ( BKPM Technology of Materials 2 ; 2002) . Blangket soil has physical characteristics such as clay or loose, white or dull yellow. This soil is found in the area Grobogan . This study tried to assess the use of the material as a mixture of blangket soil making paving blocks in terms of compressive strength. This study used an experimental method in the laboratory testing of materials POLINES Civil Engineering department, where for each of the mixtures made 3 test object. The test results indicate that the material can be used as an alternative blangket soil as a mixture of block paving to reduce and replace the use of sand material . It is shown from the results of testing compressive strength of paving blocks with a mixture of soil blangket in comparison 1PC : 4Ps : 2TB has a compressive strength of 10.75 MPa , which qualified quality block paving D ( SNI 03-0691-1996 use for a garden ). For future development needs to be done further research on the use of land blangket as material for paving blocks in terms of economics.